Something Old, Something New: Finnish Living Historical Memory in the 2010s. (April 2021) - Hakoköngäs, Eemeli; Pirttilä-Backman, Anna-Maija; Halme, Merja
In this article, the authors present new results and discuss Finnish living historical memory in the 2010s. The data was collected as part of an international online survey in 2018–2019. The authors analyze the responses of 303 Finns who were asked to list three of the most influential events in Finnish history that had occurred in their lifetime or in the lifetime of someone they knew or had known. Cluster analysis is used to gain insight into the heterogeneous set of events that the respondents recalled. Finnish membership of the European Union (1995), recent global upheavals (e.g., 9/11), and historically more distant wars (1939–1944) characterize living historical memory. Five clusters—internationalizing nation, threatened nation, surviving nation, in favor of the European Union, and against the European Union—were discovered. Standpoints with regard to the European Union divide the respondent group. Political party preference and the level of identification with the world as a whole are related to cluster membership. Despite the differences in the level of identification and political orientation, the study shows a relatively homogeneous way of remembering events of the last century.